Room Loan Information System at the National University Web-Based: Room Loan Information System at the National University Web-Based - Angga Pradihta; Septi Andryana; Benrahman Benrahman (Jurnal Mantik, 2020)
The National University conducts daily lecture activities. In addition, the National University has several activities outside of lectures that use space in the campus building so that the activities can run well. In borrowing a room, students still have to ask the schedule directly by visiting the room provider. Which still requires quite a long time. Room lending system is a system that can overcome problems for room lending at the National University. Submitting a loan can be done online. Every loan will be saved by the system. With this application it is hoped that it can help to make it easier to use to make room loans more easily and efficiently.